2020
DOI: 10.1108/ijoem-11-2019-0983
|View full text |Cite
|
Sign up to set email alerts
|

Relational capital, service quality and organizational performance in the Egyptian telecommunication sector

Abstract: PurposeThe purpose of this paper is to empirically investigate the mediating effect of service quality (SQ) in the relationship between relational capital (RC) and organizational performance (OP) within the Egyptian mobile telecommunication setting.Design/methodology/approachA valid research instrument was utilized to conduct a survey of 384 top- middle- and supervisory- level managers from three Egyptian mobile telecommunications companies. The hypothesized direct relationships were tested through multiple li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Relational capital is one of the important factors in promoting innovation and improving organisations' innovation performance because it enhances acquisition of external knowledge, which can then be integrated with the internal knowledge of the organisation. The newly accumulated knowledge through long-term external and internal cooperation relationships can be used to build the organisation's capabilities (Abd-Elrahman and Kamal, 2020; Seo, 2020; Widayanti and Damayanti, 2020).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Relational capital is one of the important factors in promoting innovation and improving organisations' innovation performance because it enhances acquisition of external knowledge, which can then be integrated with the internal knowledge of the organisation. The newly accumulated knowledge through long-term external and internal cooperation relationships can be used to build the organisation's capabilities (Abd-Elrahman and Kamal, 2020; Seo, 2020; Widayanti and Damayanti, 2020).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Relational capital (RC) is commonly defined as knowledge embedded in relationships with stakeholders such as customers, suppliers, regulators, communities, pressure groups, and intermediaries (Roos et al, 1997 ; Vrontis et al, 2021 ; Cosma et al, 2019 ; Bontis, 1999 ). RC is a valuable knowledge resource that contributes to creating value and leading the overall performance and success of the organization (Abd-Elrahman and Kamal, 2020 ; Catanzaro et al, 2019 ; Kohtamäki et al, 2012 ). Owing to such positive interrelatedness, prior research has shown that the extent of mutual trust, licensing agreements, and formal contracts with third parties facilitates the knowledge integration process (Zahoor & Gerged, 2021 ; Bhatti et al, 2020 ; Roos et al, 1997 ) and consequently leads the performance of the organization (Yayla et al, 2018 ; Hult et al, 2004 ).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Relation capital (RC) refers to the value-added relationship of firms to leverage the strategic innovation process in HEIs (Abd-Elrahman and Kamal, 2020 ; Cabrilo, et al, 2018 ; Tseng & Goo, 2005 ). Prior research has shown that the knowledge production process cannot work in isolation (Cricelli et al, 2018 ; Ramírez & Gordillo, 2014 ).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Wu et al [34], Sambasivan et al [36], and Zhao et al [74] indicate relational capital is an important influence factor of organizational performance. Moreover, Abd-Elrahman and Kamal [75] indicate relational capital positively affects organizational performance, and service quality plays a mediating role between them. Yu et al [37] indicate relational capital could indirectly improve financial performance via green supply chain management.…”
Section: Effect Of Relational Capital On Organizational Performancementioning
confidence: 99%